IDENTIFICATION OF SECONDARY METABOLITES BY GAS CHROMATOGRAPHY WITH MASS SPECTROSCOPY IN CALLUS TISSUES OF CISTANCHE DESERTICOLA Y.C. MA - Sutula, M.Y.; Gubaidullin, N.N.; Rakhimzhanova, A.O.; Manabayeva, S.A. (Eurasian Journal of Applied Biotechnology, 2024)
The aim of this study is to analyze the types of secondary metabolite compounds found in cistanche (Cistanche deserticola) plants. Methanolic extracts of callus tissues and shoots (stolon) of cistanche were obtained by lyophilic drying and grinding to powdered state using 80% methanol. Secondary metabolites within cystanche callus were first identified by GC-MS (gas chromatography-mass spectroscopy). The identification results of the methanolic extracts revealed various types of compounds including fatty acids (hexadecanoic acid, methyl ester); phenolic compounds and their derivatives (phenol, 2,4-bis(1,1-dimethylethyl)-, 2-methoxy-4-vinylphenol, homovanillyl alcohol, phenol, 2,6-dimethoxy;) sterols (γ-sitosterol); sugars, glycosides and other carbohydrates (ethyl α-D-glucopyranoside, sucrose), glycols and their derivatives (tetraethylene glycol, diethylene glycol monodododecyl ether), etc. Some of the detected compounds may be precursors or by-products of phenylethanoid glycosides biosynthesis. We also found a correlation between callus color and its chemical composition of secondary metabolites. The data can be used for further optimization of C. deserticola cultivation methods to increase the content of target secondary metabolites.